Health risk analysis of microplastics in soil in the 21st century: A scientometrics review - Sun, Yitao; Yang, Chao; Liang, Huajun; Zhang, Siqi; Zhang, Ruifang; Dong, Yongli; Tanveer, Sikander Khan; Hai, Jiangbo (Frontiers in Environmental Science, 2022)
Microplastics (MPs) in soil cause severe damage to the ecological environment and organisms, and research on their health risks has received extensive attention, but there is no comprehensive review of this research. From the perspective of bibliometrics, this paper systematically and comprehensively describes the progress, trends, and hotspots of health risks of MPs in soil based on the Web of Science Core Collection (WOSCC). China is the most active country, and more than half of the top 10 active institutions are from China. This paper systematically expounds on the sources of MPs in soil, the health risks of MPs to organisms (plants, humans, and microorganisms), and control measures. Finally, some challenges and prospects conducive to the rapid and balanced development of the field of MPs health risks in soil are proposed, which provide valuable reference and help for future researchers.